Microsatellite instability in hepatocellular carcinoma in non-cirrhotic liver in patients older than 60 years - Togni, Roberto; Bagla, Nipin; Muiesan, Paolo; Miquel, Rosa; O'Grady, John; Heaton, Nigel; Knisely, Alex S; Portmann, Bernard; Quaglia, Alberto (Hepatology research, 2009)
Aim:  Hepatocellular carcinoma (HCC) in otherwise normal liver is rare, its pathogenesis remains obscure and the literature on the subject is scarce. We investigated microsatellite instability (MSI) in eight elderly patients (median age 70.7, range 63–76 years) without a clinical history of liver disease and who underwent liver resection for HCC in otherwise normal background liver between 2001 and 2005 at King's College Hospital, London. Methods:  Immunohistochemistry for mutL homolog 1 (MLH1), mutS homolog 2 (MSH2), mutS homolog 6 (MSH6) and post‐meiotic segregation increased 2 (PMS2) was carried out on formalin‐fixed and paraffin‐embedded sections of tumor and background liver. MSI analysis was performed using a panel of monomorphic microsatellites markers: BAT‐25, BAT‐26, NR21, NR24 and NR27 and pentaplex PCR. Results:  All HCC were solitary large tumors. Two also had satellite nodules. The background liver was usually unremarkable. There was nuclear expression of MLH1, MSH2, MSH6 and PMS2 in all tumors excluding a DNA mismatch repair defect. The same pattern of staining was noted in the hepatocytes of the background liver of all cases. No differences between microsatellite lengths in the background liver and in the tumor, as assessed in PCR products, were found for any of the five microsatellite markers in any patients. These findings provided no evidence for MSI. Conclusion:  Our study showed that MSI is not implicated in the pathogenesis of a subset of HCC affecting elderly patients without chronic liver disease. Further studies are needed to clarify the pathogenesis of HCC in this particular setting.